Preventing sudden death in a competitive athlete: a case report - Rossi, A.; Claiborne, T.; Fetter, J. (International Journal of Athletic Therapy & Training, 2018)
A 19-year-old male collegiate wrestler was diagnosed with bicuspid aortic valve disease and aortic insufficiency due to the presence of an aortic-ventricular tunnel. The athlete underwent an electrocardiogram, transthoracic echocardiogram, transesophageal echocardiogram, as well as a diagnostic ultrasound of his carotid arteries and abdominal aorta in order to diagnose this underlying structural abnormality. This diagnosis resulted in the athlete being disqualified for the remainder of the wrestling season and undergoing open-heart surgery to repair his bicuspid aortic valve. This case study will explain the events surrounding the recognition of this disease as well as advocate for the use of cardiac screening in preparticipation exams (PPEs). It is imperative that we implement more advanced diagnostic testing in the PPEs of young athletes in order to diagnose underlying structural heart abnormalities that may lead to sudden cardiac death.